2014
DOI: 10.1007/s00128-014-1312-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment to Glyphosate of Two Species of Annelids

Abstract: Adult mortality, biomass, fecundity and viability of cocoons were studied in Eisenia fetida and Octolasion tyrtaeum, in response to glyphosate exposure in soil. Exposure tests were carried out following USEPA procedure, with five concentrations of glyphosate in soil and a control. O. tyrtaeum was more sensitive to the highest concentration of glyphosate (50,000 mg kg(-1)), with 100 % mortality by day 7 of exposure, compared with 71 % for E. fetida. Although biomass of O. tyrtaeum was significantly different be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
3
23
1
Order By: Relevance
“…Garc ıa-P erez, Alarc on-Guti errez, Perroni, & Barois, 2014; Garc ıa-Torres, Giuffr e, Romaniuk, R ıos, & Pagano, 2014;Gaupp-Berghausen, Hofer, Rewald, & Zaller, 2015;Givaudan, Binet, Le Bot, & Wiegand, 2014) and to date, the results vary from negative to no effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garc ıa-P erez, Alarc on-Guti errez, Perroni, & Barois, 2014; Garc ıa-Torres, Giuffr e, Romaniuk, R ıos, & Pagano, 2014;Gaupp-Berghausen, Hofer, Rewald, & Zaller, 2015;Givaudan, Binet, Le Bot, & Wiegand, 2014) and to date, the results vary from negative to no effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been some reports of harmful effects on microorganisms, insects and frogs, which has prompted increased interest in investigating its potential adverse effects on field populations of earthworms (e.g. García‐Pérez, Alarcón, Hernández, & Hernández, ; García‐Pérez, Alarcón‐Gutiérrez, Perroni, & Barois, ; García‐Torres, Giuffré, Romaniuk, Ríos, & Pagano, ; Gaupp‐Berghausen, Hofer, Rewald, & Zaller, ; Givaudan, Binet, Le Bot, & Wiegand, ) and to date, the results vary from negative to no effect.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Piola et al [61] found that lethal rates depended on commercial herbicide formulations. Regarding reproduction parameters, the number of juveniles and/or cocoons decreased at rates of 1 to 1000 mg¨kg´1 [55], 5000 mg¨kg´1 [60] and 1440 mg¨ai¨ha´1 [54]. However, other studies found no significant effects of glyphosate on measured earthworm reproduction parameters [53,56,57,62].…”
Section: Land Uses and Management Systems In Argentine Pampasmentioning
confidence: 89%
“…at recommended (from 1440 g ai/ha to 1800 g ai/ha) and higher rates of glyphosate [53][54][55][56][57][58][59][60]. García-Torres et al [60] reported significant mortality at only very high concentrations (50,000 mg¨kg´1). Finally, Piola et al [61] found that lethal rates depended on commercial herbicide formulations.…”
Section: Land Uses and Management Systems In Argentine Pampasmentioning
confidence: 98%
“…The soil properties impeded a consistent assessment of toxicity for D. annae . Octolasion tyrtaeum , an earthworm from Argentinean agroecosystems, has also been tested with glyphosate and was found to be more sensitive than E. fetida . The earthworm tests with A. gracilis and D. annae were performed with organisms collected from the field because they could not be cultured in the laboratory.…”
Section: Why Focus On Soil Ecotoxicology In Latin America?mentioning
confidence: 99%